CD38 Deficiency Promotes Inflammatory Response through Activating Sirt1/NF-κB-Mediated Inhibition of TLR2 Expression in Macrophages - Yisong Qian; Chuqiao Chen; Leliang Ma; Ziwei Wang; Ling-Fang Wang; Li Zuo; Yaqin Yang; Xiang Huang; Meixiu Jiang; Xiaolei Wang; Huidong Shi; Mingui Fu; et al. (Mediators of Inflammation)
CD38 was first identified as a lymphocyte-specific antigen and then has been found to be widely expressed in a variety of cell types. The functions of CD38 are involved in numerous biological processes including immune responses. Here, we showed the downregulations of both TLR2 mRNA and protein in macrophages from CD38−/− mice and in CD38 knockdown RAW264.7 cells. Several NF-κB-binding motifs in the promoter region of the TLR2 gene were identified by the bioinformatics analysis and were confirmed by the luciferase activity assay with the different truncated TLR2 promoters. CD38 deficiency resulted in the reduction of NF-κB p65 and acetyl-NF-κB p65 (Ac-p65) levels as determined by Western blot. The expression of Sirt1 did not change, but an increased activity of Sirt1 was observed in CD38-deficient macrophages. Inhibition of the Sirt1/NF-κB signaling pathway resulted in downregulation of TLR2 expression in RAW264.7 cells. However, re-expression of CD38 in the knockdown clones reversed the effect on Sirt1/NF-κB/TLR2 signaling, which is NAD-dependent. Moreover, the inflammatory cytokines including G-CSF, IL-1alpha, IL-6, MCP-1, MIP-1alpha, and RANTES were increased in CD38 knockdown RAW264.7 cells. Taken together, our data demonstrated that CD38 deficiency enhances inflammatory response in macrophages, and the mechanism may be partly associated with increased Sirt1 activity, which promoted NF-κB deacetylation and then inhibited expression of the TLR2 gene. Obviously, our study may provide an insight into the molecular mechanisms in CD38-mediated inflammation.